Resistance of frozen-thawed epididymal and ejaculated spermatozoa of buffalo bulls - GUPTA, H P; SAHNI, K L; MOHAN, G (The Indian Journal of Animal Reproduction, 2023)
Storage and thermal resistance (per cent motile sperm at 5°C and 37°C, respectively) of frozen-thawed buffalo epididymal spermatozoa were studied in comparison to ejaculated ones. Storage thermal resistance were significantly (P<0.01) higher in epididymal semen than in the ejaculated one at all periods of storage/incubation.